The impact of internet-based cognitive behavioral therapy on mental health outcomes and life in breast cancer patients: a systematic review and meta-analysis - Han, Jianlong; Ding, Yunxin; Wang, Hongwei; Li, Qing; Zhai, Huanqie (Frontiers in Oncology, 2024)
BackgroundInternet-based cognitive behavioral therapy(ICBT) improves the impact of breast cancer through online platforms, modular learning, goal setting, relaxation exercises, and other techniques. Compared to traditional cognitive behavioral therapy (CBT), ICBT offers advantages such as the convenience of flexible time and location choices and reduced manpower requirements. In recent years, research exploring the impact of ICBT on breast cancer patients has been increasing, with conflicting results across different studies. Therefore, the purpose of this study was to comprehensively examine the impact of ICBT on the psychological health and quality of life of breast cancer patients through a systematic review and meta-analysis.MethodsWe searched ten databases in both English and Chinese, with the search period extending from the inception of the databases to December 30, 2023. Literature screening, bias risk assessment, data extraction, and evidence level evaluation were independently conducted by two researchers. All the data were analyzed using RevMan 5.4 and Stata 17.0 software.ResultsA total of 2079 breast cancer patients were included in this study, of which 1171 patients received ICBT treatment. The results show that ICBT can reduce anxiety [SMD=-0.19, 95%CI (-0.37, -0.01), P=0.0008] and depression [SMD=-0.20, 95%CI (-0.37, -0.02), P=0.001], alleviate fatigue [SMD=-0.34, 95%CI (-0.67, -0.01), P=0.04], and improve quality of life [SMD=0.20, 95% CI (0.03, 0.38), P=0.02] in breast cancer patients. However, the intervention effects of ICBT on insomnia [SMD=-0.44, 95%CI (-0.93, 0.06), P=0.08] and sleep quality [SMD=-0.14, 95%CI (-0.30, 0.01), P=0.06] in breast cancer patients are not significant. The subgroup analysis showed that when the intervention period is longer than 8 weeks, the number of intervention modules exceeds 6, and a waitlist control group is included, there is a significant effect on reducing patients’ anxiety and depression. However, the method of guidance and whether the intervention period exceeds 12 weeks are not related.ConclusionICBT can alleviate anxiety and depression in breast cancer patients, with the intervention effects being independent of the guidance method. Significant results were obtained when the intervention period was >8 weeks and the number of modules was >6. ICBT can reduce fatigue and improve quality of life in breast cancer patients, but its impact on sleep quality was not significant. More high-quality research is needed in the future.Systematic review registrationPROSPERO, identifier CRD42024494744.